Writing plans instead of eliminating risks: How can written safety artefacts reduce safety?. (July 2022) - Hutchinson, Ben; Dekker, Sidney; Rae, Andrew
Highlights: A theoretical paper exploring the intersection of written safety artefacts, symbolism and a decoupling of safety. Written safety artefacts can have multiple purposes and not all of these purposes are strictly functional. Some artefacts can facilitate work to commence past an organisational block or constraint, such as a contractual requirement, which we call "enabling devices" Sometimes documents acting as enabling devices can be decoupled from the actual degree of operational risk, with some mechanisms explored in this paper. Abstract: Safety Management Systems are developed to help manage occupational risk, but they can also increase an organisation's exposure to risk. This contradictory effect may happen when written artefacts (plans, risk assessments etc.) enable work to happen by encouraging a belief that the risks have been managed, when in reality they have not been. In this paper we introduce the term "enabling device" to cover the situation where a written artefact facilitates the commencement of work. We explore how enabling devices can become excessively symbolic, where they facilitate work to commence even when they may be decoupled from the issues they were designed to manage. We argue that highly symbolic artefacts acting in their enabling function: a) become more speculative than functional, b) make assumptions and beliefs "appear more real" by giving them an observable form, c) fill a need for people to solve issues without actually having to solve the issue, and d) increasingly become the unit of management instead of the issues and then take on a life of their own. This work suggests that practitioners should more critically evaluate the often invisible and potentially pervasive symbolism vested in safety artefacts to direct effective and sustainable risk interventions.